AKTUALISASI KONSEP DAGANG SUKU TRANSMIGRASI JAWA DAN AKULTURASI BUDAYA DI TANAH MANDAR YANG DIADAPTASIKAN SEBAGAI SUMBER PEMBELAJARAN PENDIDIKAN KARAKTER KEWIRAUSAHAAN - Sakinah Fitri; Lulu Isnaeni; Siti Nur Fadillaturisqui (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The success of social doctrine and philosophy of life the Javanese, which is used to run entrepreneurs oh the land where they migrate that is, Polewali Mandar (land of Mandar) made researchers interested in the study the commercial concept (entrepreneurship) in addition is the predominantly tribal entrepeneurship profession Java became a symbol of success. Teachings social and life philosophy apply humanity, relationships in interactions include indigo patience, rila, nrima, perseverance, temen, and tepa slira and the trade ethic “Tuna Sathak Bathi Sanak”are adapted to everyday life in entrepeneurship for the same principles as Ngedulur (family/interaction ). This study aims to make allowances of the traditional trade concepts inherent in Java transmigration tribe and in the field of entrepeneurship.The method used is the qualitative method through the approach symbolic interaction with data gathering techniques through an ob interview, observation, and literature studies. The results of the research are, 1. Learning resources of the concept of trade of Javanese transmigration tribes in mandar land which are adapted to entrepeneurship which are very dynamic and relevant to the development of entrepenurship education. 2, The teachings of social values and the philosophy of life in Javanese trade are seen as appropriate in cultivating the true character of entrepreneurs and. 3, The Javanese who are successful in improving the economy and living in harmony in their transmigration places are seen as representative as role models in the environment of economic ectivity. Keywords:social teachings, trade ethos, Javanese transmigration, entrepreneurial character